Fiscal Policy and the Current Account. (IMF Working Papers; Working Paper ;, 2010)
This paper examines the relationship between fiscal policy and the current account, drawing on a larger country sample than in previous studies and using panel regressions, vector autoregressions, and an analysis of large fiscal and external adjustments. On average, a strengthening in the fiscal balance by 1 percentage point of GDP is associated with a current account improvement of 0.2-0.3 percentage point of GDP. This association is as strong in emerging and low-income countries as it is in advanced economies; and significantly higher when output is above potential.